Immunization Information Systems to Increase Vaccination Rates: A Community Guide Systematic Review. (May 2015) - Groom, Holly; Hopkins, David P.; Pabst, Laura J.; Murphy Morgan, Jennifer; Patel, Mona; Calonge, Ned; Coyle, Rebecca; Dombkowski, Kevin; Groom, Amy V.; Kurilo, Mary Beth; Rasulnia, Bobby; Shefer, Abigail; et al.
Abstract : Context: Immunizations are the most effective way to reduce incidence of vaccine-preventable diseases. Immunization information systems (IISs) are confidential, population-based, computerized databases that record all vaccination doses administered by participating providers to people residing within a given geopolitical area. They facilitate consolidation of vaccination histories for use by health care providers in determining appropriate client vaccinations. Immunization information systems also provide aggregate data on immunizations for use in monitoring coverage and program operations and to guide public health action. Evidence Acquisition: Methods for conducting systematic reviews for the Guide to Community Preventive Services were used to assess the effectiveness of IISs. Reviewed evidence examined changes in vaccination rates in client populations or described expanded IIS capabilities related to improving vaccinations. The literature search identified 108 published articles and 132 conference abstracts describing or evaluating the use of IISs in different assessment categories. Evidence Synthesis: Studies described or evaluated IIS capabilities to (1) create or support effective interventions to increase vaccination rates, such as client reminder and recall, provider assessment and feedback, and provider reminders; (2) determine client vaccination status to inform decisions by clinicians, health care systems, and schools; (3) guide public health responses to outbreaks of vaccine-preventable disease; (4) inform assessments of vaccination coverage, missed vaccination opportunities, invalid dose administration, and disparities; and (5) facilitate vaccine management and accountability. Conclusions: Findings from 240 articles and abstracts demonstrate IIS capabilities and actions in increasing vaccination rates with the goal of reducing vaccine-preventable disease. Abstract : This article provides findings from 240 articles and abstracts demonstrating immunization information system capabilities and actions in increasing vaccination rates with the goal of reducing vaccine-preventable disease.